Screening for retinopathy of prematurity in neonates - Kasundra, Mitul; Patel, Purvi; K. M., Mehariya (International Journal of Research in Medical Sciences, 2016)
Background: Retinopathy of prematurity (ROP) is a vaso-proliferative disorder of the retina among preterm infants. Neonates born at less than 32 weeks of gestation are at risk of developing ROP. However preterm infants born at 32 weeks or later can also develop severe ROP if they had turbulent NICU course or required prolonged oxygen therapy. Aims of the study were to determine incidence, risk factors of ROP in neonates and to determine the association of birth weight, gestational age and incidence of ROP. Methods: Prospective analytic study done in indoor patients in neonatal intensive care unit at a tertiary care center from June 2015 to May 2016. Results: Overall incidence of retinopathy of prematurity in preterm neonates is 18.4%. Incidence increases with decreasing gestational age. In preterm <28 weeks of gestational age, incidence of ROP is 35%. Incidence also increases with decreasing birth weight. Incidence of ROP in neonates with birth weight less than 1.25kg is 50%. Risk factors include prematurity, oxygen therapy, septicemia, intraventricular hemorrhage, anemia needing blood transfusion. Most patients of ROP have stage-1 disease (76%). The twenty one cases having ROP underwent laser ablative therapy. Earlier detection by screening leads to early intervention and prevention of blindness. Conclusions: The timely retinal screening of high-risk preterm infants is important to prevent the development of advanced ROP. Since ROP may produce serious sequel up to complete blindness, all efforts must be made to prevent the development of advanced ROP through elimination of preterm births, changes in the neonatal care and improvement in detection of threatening ROP markers.